Identification of Suitable Villages for Agritourism Development (A Case Study of Semirom County) - Narges Vazin; Ali Sadeghi; Zahra Barati (برنامه ریزی فضایی)
Abstract  Agricultural tourism has been recognized as an opportunity for rural development in recent decades. To promote sustainable agricultural tourism, identifying and prioritizing villages suitable for the development of this activity is essential. This research aims to locate suitable villages for the development of agritourism in rural areas of Semirom County. The method used is a survey-analytical approach. The study population consists of experts and farmers. Data collection was done through questionnaires. Initially, suitable indicators were identified through the opinions of 15 experts using the fuzzy analytic hierarchy process and Super Decision software. Then, using spatial indicators through ArcGIS software and the fuzzy overlay method, areas and villages suitable for agritourism development were determined, ultimately selecting 14 villages based on population size. In the next stage, the social capacity of the local community in the identified villages was assessed. Data were collected from 326 individuals using questionnaires and analyzed with SPSS software. Finally, using the TOPSIS model, villages were ranked based on all indicators influencing agricultural tourism development, including natural and tourism resources, tourism infrastructure, and the social capacity of the local community. The results indicated that Aliabad, Dangzalu, and Khafar have the highest potential for agritourism development. Furthermore, the results showed that planners should consider all factors including agricultural capacity, natural resources, tourist attractions, infrastructure, and local social capacity when identifying suitable villages for agritourism. Keywords: Agritourism, Agritourism Prone Area Determination, Rural Areas, Fuzzy Analytic Hierarchy Process, Semirom County. IntroductionAgritourism is a type of tourism that allows visitors to learn and experience agricultural activities and rural lifestyle. Nowadays, agritourism is recognized as an approach to sustainable development of rural areas. Agritourism can transform local resources into tourism products and services, as well as provide real opportunities for the development of rural communities. Therefore, it is important to locate suitable villages for the development of agritourism. One of the key challenges in locating suitable areas for agritourism development is providing a framework and appropriate techniques for evaluating the suitability of a location for this type of tourism. To create and develop agritourism destinations, attention must be paid to all the region's potential such as the environment, agricultural products, cultural attractions, and infrastructure that meet the needs of tourists during their visits.The aim of this research is to identify suitable criteria for determining villages suitable for agritourism development and locating suitable villages for agritourism development in Semirom County. Different methods including GIS, fuzzy AHP, statistical analysis, and TOPSIS have been used to determine suitable villages for agritourism development due to the use of various qualitative and quantitative criteria. The study area is Semirom County in Isfahan Province, known as the horticultural hub of Isfahan Province. In addition to its agricultural capacities, with various natural, cultural, and historical attractions, it is a suitable destination for agritourism development, attracting many tourists annually to visit the villages and orchards in this area. Materials and MethodsThe research method is a descriptive-analytical type carried out using a survey method and the quantitative approach. The research area is the villages of Semirom County. Initially, research indicators were identified through literature review and expert consultation. Then, they were evaluated by 15 experts using the Fuzzy Analytic Hierarchy Process (Fuzzy AHP) model and Super Decision software to determine the final weights of the indicators. The suitable zones and villages for agricultural tourism were identified based on spatial criteria. To identify the appropriate zone, a map was prepared for each indicator based on the weights of the indicators and analysis scale using ArcGIS software. Subsequently, by combining the maps using the Fuzzy Overlay and Fuzzy Gamma operators, the final map was prepared. In the next step, the social capacity of the local community in villages suitable for agritourism was evaluated. The target population of the study consisted of farmers in the identified villages. A researcher-made questionnaire was used for data collection. SPSS software and descriptive and one-sample t-tests were employed for data analysis. Finally, the identified suitable villages were prioritized based on all indicators using the TOPSIS model. Research FindingsBased on the research findings, 29 indicators were identified for locating villages suitable for agritourism development. The indicators of orchard area and agricultural land area were identified as the most important indicators for locating villages suitable for agritourism. Additionally, indicators such as climate, proximity to water sources, diversity of vegetation, and proximity to protected areas were also identified as important indicators in agritourism development. To identify suitable villages, after preparing a map for each of the indicators, by combining the maps using the fuzzy overlay function and gamma operator, a map of zones and villages suitable for agritourism development was prepared. According to the final map, 4.66% of the province's area, including 14 villages in the southwestern, central, and northwestern parts of Semirom County, was identified as the most suitable zone for agritourism development. The social capacity status of farmers in villages located in the very suitable category was evaluated, showing that farmers in these villages understand the positive effects of agritourism on their village and businesses and are willing to engage in agritourism activities. However, the farmers' capacity to offer various agricultural tourism activities, including developing recreational activities and organizing ceremonies and festivals, is lower than desirable. After ranking the villages based on all indicators using the TOPSIS model, the villages of Aliabad, Dangzalu, and Khafar were recognized as the most suitable villages for agritourism development. Discussion of Results and ConclusionsThe results indicate that agricultural capacities and natural resources are key criteria in agritourism development. In addition to natural attractions, the development and sustainability of agritourism depend on the unique cultural heritage of the village, tourism infrastructure, and the capacity of the local community. The present study provides a comprehensive analysis of the spatial distribution of agricultural capacities, tourism resources and attractions, infrastructure, and local community capacity, which can assist regional planners in identifying and implementing the best strategies for agricultural tourism development. This research presents a zoning map with different categories ranging from very suitable to very unsuitable and ranks the most suitable villages for agritourism development. The results will be practical for planners and regional officials in selecting a suitable village for investment and agritourism development.